أهمية دراسة الصوائت العربية في إيضاح المعنى لدى الناطقين بغير العربية = The importance 0f learning Arabic vowel system among non-native speakers in determining the lexical meaning of Arabic words - Ahmed Mohamed, Ismaiel Hassanein; Mohd Noor, Shamsudin (2015)
نىاث ال غٗب تُ، زهىنا